Penggunaan Metode CRI (Certainty Of Response Index) Berbantuan Soal PISA (Programme Of International Student Assesment) untuk Mengidentifikasi Miskonsepsi IPA Materi Tata Surya - Rachmawati, Sekar; Susanto, Hadi; Fianti, Fianti (UPEJ Unnes Physics Education Journal, 2017)
PISA's results show that math and science education in Indonesian students is very low. One of the causes of the poor quality of education in Indonesia is the lack of understanding of concepts and misconceptions. This study aims to determine the various misconceptions of junior high school students in the solar system. The design of this study is survey research with sampling using simple random sampling obtained class VII B and VII C. Methods of data collection with PISA-assisted tests, questionnaires and interviews. The result of the research shows the misconception level on the concept of sea tidal rise of 34%, the concept of rotation of the Earth by 26%, the concept of the Earth revolution by 36%, the concept of the Sun as a star of 36%, the concept of the Sun which has 23% The moon is 43%, the concept of rotation and the revolution of the Moon is 36%, the concept of urban and rural observation of the stars by 33%, the concept of meteoroid, meteor and meteorite by 47%, the concept of Kepler's third law by 31% Planet type and its orbital velocity by 36%, the concept of the second law of Keppler by 41%, the concept of the gravitational force between the Sun and the planet by 39%, the concept of Newton's law of gravity of 27%